Development of hybrid composites using treated natural biofibers and nanoparticles for structural applications. Issue 1 (June 2020) - Banapurmath, N R; Patil, Arun; Ahmed, Rehan; Kurdeka, Rahul
Abstract: Tiger grass which is inculcated in reinforcements with combining with Polypropylene(PP) emusled as a resine scorted by individual combination with verity of different nano particles resulting with a composite materials incorporated in real structural applications. Adherence between the nanofillers with bonding matrix was enhanced with combination of alkalization &KMnO4 treating methodsto enhance or cultivate on biofibresurface. Three different types of nanofillers with different percentage combination were made separately. Certain mechanical testing was encapsulated under 3 point bending and tensile stress loading to obtain mechanical properties such as deflection due to loading and obtaining tensile strength of respective sample beams. The bioreinforced composite was also tested by Thermo Gravimetric Analysis (TGA) to understand the methodology for degradation with rising temperature. For this reason, there must be microscopically test taken up like scanning electron microscope (SEM) was carried out. Based on the obtained results, when the chemically induced biofibres amalgamated along nanofillers with certain percentage, displayed striking better mechanical properties than the biofibres which were untreated.. Among the results, out of 3 different nanofiller combined with treated natural fibers, h-Bn with 0.3% of weight of fibres treated with consulted percent composition near to 5% NaOH along with 0.6% of KMnO4 gave acceptablemechanical testing propertiesas compared to other graphine, graphine platelets and nontreated bio-fibre composites.